2015
DOI: 10.3389/fmicb.2015.01172
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic impact on diazotrophic diversity in the mangrove rhizosphere revealed by nifH pyrosequencing

Abstract: Diazotrophs in the mangrove rhizosphere play a major role in providing new nitrogen to the mangrove ecosystem and their composition and activity are strongly influenced by anthropogenic activity and ecological conditions. In this study, the diversity of the diazotroph communities in the rhizosphere sediment of five tropical mangrove sites with different levels of pollution along the north and south coastline of Singapore were studied by pyrosequencing of the nifH gene. Bioinformatics analysis revealed that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…Of the five sampling locations selected, SJ was the least influenced by human activities. We therefore used this pristine location on the southern coastline of Singapore as the background as we have done in a previous study [ 32 ]. SJ contained the lowest concentration of dissolved inorganic nitrogen (DIN), when compared with the other locations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the five sampling locations selected, SJ was the least influenced by human activities. We therefore used this pristine location on the southern coastline of Singapore as the background as we have done in a previous study [ 32 ]. SJ contained the lowest concentration of dissolved inorganic nitrogen (DIN), when compared with the other locations.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study on diazotrophs, we recovered various SRB including Desulfobotulus , Desulfarculus , Desulfonatronum and Desulfovibrio , from the mangrove rhizospheres in the same sampling locations we used for this study. We found that they were more abundant in the pristine location at SJ (~40%) than in the most polluted location at SC (~4%) [ 32 ]. Their presence indicates not only the potential for bioremediation and the resiliency of the ecosystem to anthropogenic impact, but their coexistence with methanogens in different niches is very likely supported by different substrates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations